2017
DOI: 10.1167/iovs.17-21480
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monocyte Chemoattractant Protein 1 Prevents Conjunctival Fibrosis in an Experimental Model of Glaucoma Filtration Surgery

Abstract: Targeting MCP-1 results in prolonged bleb survival following experimental GFS with less cellular toxicity as compared to MMC. MCP inhibition could provide a safer alternative to conventional antifibrotic adjunctive treatments in GFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Among these growth factors, the levels of several factors such as TGF-β, VEGF, CTGF, and MCP-1 increased in the AH in POAG, XFG, or neovascular glaucoma patients, which suggests that these factors stimulated the signaling pathway leading to myofibroblast transdifferentiation of HCFs, monocyte-derived cell infiltration, and ECM remodeling after trabeculectomy 11 , 13 15 , 27 . Several in vivo and in vitro studies have suggested that modulation of these factors could be used as a novel strategy to control scarring after trabeculectomy 13 , 14 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these growth factors, the levels of several factors such as TGF-β, VEGF, CTGF, and MCP-1 increased in the AH in POAG, XFG, or neovascular glaucoma patients, which suggests that these factors stimulated the signaling pathway leading to myofibroblast transdifferentiation of HCFs, monocyte-derived cell infiltration, and ECM remodeling after trabeculectomy 11 , 13 15 , 27 . Several in vivo and in vitro studies have suggested that modulation of these factors could be used as a novel strategy to control scarring after trabeculectomy 13 , 14 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Common between both in vivo and in vitro profiles is the specific modulation of CCL2 and several members of the interleukin family. Elevated CCL2 is implicated in greater risk of scarring in glaucoma surgery [ 37 , 38 ]. The capacity of VPA to suppress these cytokines, particularly CCL2 and VEGF-A, by steady-state conjunctival fibroblasts, suggests that pre-treatment with VPA may be advantageous for preempting the full cascade of the inflammatory and angiogenic responses in the aftermath of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal models provide the major advantage of producing readily available biological samples to perform multiple assays on. This has enabled the development of studies that make use of objective quantitative methods such as real‐time polymerase chain reactions to study genetic alterations in experimental glaucoma filtration surgery, as well as histological research that evaluates differences in inflammatory cell populations in terms of cell proliferation/density, cell toxicity and changes in the extracellular matrix (Seet et al; 2010; Chong et al 2017). Changes in the inflammatory cell profile mediate scarring predisposition due to the increased secretion of profibrotic cytokines, together with the deposition of extracellular matrix proteins such as collagen and fibronectin that are important modulators of wound healing.…”
Section: Considerations When Evaluating Animal Models Of Glaucoma Filmentioning
confidence: 99%
“…An example of these imaging methods is shown in Fig. 1 (Chong et al 2017). Capsular porosity has also been postulated to be a major determinant of fluid outflow (Gardiner et al 2010) and has been studied in rabbits following the implantation of intracameral drainage devices (Nguyen et al 2012; Pandav et al 2016) where the authors found that infusions of balanced salt solution at physiological pressures in the absence of inflammatory cytokines were sufficient to alter the porosity of the fibrous capsule at the surgical site.…”
Section: Considerations When Evaluating Animal Models Of Glaucoma Filmentioning
confidence: 99%